Evaluation of strains and thicknesses of pipe elbows on the basis of expressions resulting from the eu-directive for the case of large and small deformations - Śloderbach, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
The relations to calculate the maximum value of strains in processes of bending tubes on benders, in stretched layers of tubes, are presented in this work on the basis of the EU-Directive concerning production of pressure equipment. It has been shown that for large deformations that occur during bending of the pipes on knees, logarithmic strain measures (real) and relative strain measures give different values of strain but equal wall thicknesses in the bending zone.
Keywords: EU Directive; required thicknesses of pipe elbows; pipe bending processes; relative and logarithmic measures of deformation; required initial thickness of a bent tube